Solid-like smooth anti-icing and deicing coating with multi-scale photo-thermal trap and preparation method thereof
By introducing multi-scale hollow microspheres and carbon aerogel into the coating, an anti-icing and de-icing coating with multi-scale photothermal traps was prepared, which solved the problems of low icing and frosting efficiency and poor durability of aerospace components in the prior art, and achieved a highly efficient and durable anti-icing and de-icing effect.
Patent Information
- Application Number
- CN202511443067.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-10
- Publication Date
- 2025-12-09
AI Technical Summary
In the existing technology, the methods for preventing and removing icing and frost on aerospace components are inefficient and energy-intensive, and passive anti-icing coatings fail or have poor durability in low-temperature and high-humidity environments.
By introducing multi-scale micro-nano-nano scale hollow microspheres into the coating, combined with carbon aerogel and hollow thermoplastic acrylate microspheres, a solid-like slippery anti-icing coating with multi-scale photothermal traps is prepared, and efficient anti-icing is achieved by utilizing photothermal conversion and nanoporous structure.
It exhibits excellent de-icing performance in extremely cold environments, extending the freezing delay time by 80 times and reducing the ice adhesion strength by 22.7 times. It possesses high hydrophobicity, low sliding angle, and excellent photothermal de-icing capability, as well as UV resistance and stable silicone oil storage capability.
Smart Images

Figure CN121086629A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of deicing coatings, in particular to a solid-like smooth anti-icing and deicing coating with multi-scale photothermal traps and a preparation method thereof. BACKGROUND
[0002] In the aviation industry and the like, icing and frosting are extremely harmful, for example, icing and frosting of aircraft components can damage the smoothness of the airfoil shape, affect flight control and even cause air disasters. The existing active deicing and defrosting method has low efficiency and high energy consumption, and is difficult to be applied on a large scale. The passive anti-icing super-hydrophobic surface (SHS) and the smooth liquid-impregnated porous surface (SLIPS) also have defects, the former fails in a low-temperature and high-humidity environment, and the performance of the latter deteriorates due to the loss of lubricant. SUMMARY
[0003] The application provides a solid-like smooth anti-icing and deicing coating with multi-scale photothermal traps and a preparation method thereof, aiming at the problems of low photothermal efficiency of the existing photothermal coating and poor durability of the SLIPS coating. The solid-like smooth anti-icing and deicing coating with multi-scale photothermal traps is prepared by introducing multi-scale hollow structure microspheres of micro-nano-nanometer scale into the coating, and the coating has high efficient anti-icing characteristics and durability. The solid-like smooth anti-icing and deicing coating with multi-scale photothermal traps has excellent ice-repellent performance in an extreme cold environment (such as a low-temperature and high-humidity environment). The method is simple and easy to operate, does not need to use special instruments and equipment, and has high operability and is easy to be industrialized.
[0004] The application is realized by the following technical scheme:
[0005] The application relates to a preparation method of a solid-like smooth anti-icing and deicing coating with multi-scale photothermal traps. Anion-modified carbon aerogel (CAA) photothermal nanoparticles are deposited on the surface of cation-modified hollow thermoplastic acrylate microspheres (TAM), and the TAM@CAA microspheres are obtained by suction filtration and drying. Then, the surface of the microspheres is in-situ grown with silica (SiO2) aerogel by alkali catalysis sol-gel method, and the TAM@CAA@SiO2 multi-scale photothermal trap microspheres are obtained by suction filtration and freeze-drying. Then, the multi-scale photothermal trap microspheres, silicone oil (SO) and a curing agent are dispersed into an organic solvent containing epoxy resin to form a prepolymer, and the solid-like smooth anti-icing and deicing coating with multi-scale photothermal traps is obtained by spin coating and curing.
[0006] The anion modification refers to that the carbon aerogel (CAA) photothermal nanoparticles are dispersed into an anion modification liquid, and the CAA is dried at 80 DEG C for 12 hours after room temperature reaction for 8-12 hours.
[0007] The specific surface area of the CAA is 666.20 m 2 / g.
[0008] The anion modification liquid is NaOH aqueous solution, and the concentration is preferably 0.5-1.5 mol / L.
[0009] The mass ratio of the CAA photothermal nanoparticles to the NaOH aqueous solution is 1:100.
[0010] The cation modification refers to dispersing TAM into a cation modification liquid, drying at 80 DEG C for 12 hours after reaction at room temperature for 8-12 hours.
[0011] The cation modification liquid is polydiallyldimethylammonium chloride (PDDA), polyethyleneimine (PEI) or cationic polyacrylamide (CPAM) aqueous solution, and the concentration is preferably 1-2 mol / L.
[0012] The mass ratio of the TAM to the cation modification aqueous solution is 1:50.
[0013] The deposition refers to dispersing the cation modified TAM and the anion modified CAA in a solvent according to a mass ratio of 1:1-2 (cation modified TAM:anion modified CAA), and the reaction solvent is deionized water, and the reaction time is 4-12 hours; and the TAM@CAA microspheres are obtained after drying at 80 DEG C for 12 hours after the reaction.
[0014] The mass ratio of the deposition solvent deionized water to the cation modified TAM and the anion modified CAA is 100:1:1-2.
[0015] The base catalyzed sol-gel method refers to mixing and dispersing the TAM@CAA microspheres and a silicon source into a blended solution of deionized water and ethanol, and further adding a base catalyst and fully reacting.
[0016] The mass ratio of the TAM@CAA microspheres to the silicon source is 1-2:1.
[0017] The silicon source is tetraethyl orthosilicate (TEOS), sodium silicate (Na2SiO3) or methyltrimethoxysilane (MTMS).
[0018] The mass ratio of deionized water to anhydrous ethanol in the blended solution is 1:0.5-1.5.
[0019] The mass ratio of the silicon source to ethanol is 1:25.
[0020] The base catalyst is aqueous ammonia solution, and the concentration is 0.2-0.6 mol / L, and the weight fraction is 10.
[0021] The full reaction refers to in-situ growing SiO2 aerogel on the surface of TAM@CAA for 0.5-1.5 hours, and then freezing for 24 hours in a-20 DEG C refrigerator after suction filtration, and then freeze drying for 72 hours.
[0022] The organic solvent is ethyl acetate, and the weight fraction is 500 parts.
[0023] The mass ratio of the multi-scale photothermal trap microspheres to the silicone oil is 0.8-1.2:1, and the weight fraction is 80-120:100.
[0024] The mass ratio of the curing agent to the epoxy resin is 0.6-1.8:1, and the weight fraction is 60-180:100.
[0025] The curing agent is gamma-aminopropyl triethoxysilane, ethylenediamine or 4,4'-diaminodiphenyl methane.
[0026] The epoxy resin is E44 type, E42 type or E51 type epoxy resin.
[0027] The pre-polymer is reacted for a period of time, which is 8h at room temperature and then 0.5-1.5h at 60-100 DEG C.
[0028] The spin coating is cured, preferably at a temperature of 25-80 DEG C for 12-36h.
[0029] Technical effects
[0030] The present application combines low thermal conductive hollow thermoplastic acrylic ester microspheres, nano-porous carbon / silicon aerogel, silicone oil and epoxy resin to synergistically construct a micro-nano multi-scale photothermal trap internal structure and a solid-like smooth surface coating, so that the preparation of a solid-like smooth ice-repellent coating with a multi-scale photothermal trap is realized. The coating prepared by the present application has high hydrophobic angle and ultra-low water sliding angle (<5 DEG), extremely low ice adhesion strength, high photothermal conversion and environmental tolerance. Compared with bare aluminum, the icing delay time of the present application is prolonged by nearly 80 times, and the ice adhesion strength is reduced by 22.7 times compared with bare aluminum. In addition, the photothermal properties of CAA and the multi-scale photothermal trap structure formed by TAM@CAA@SiO2 microspheres also endow the coating with excellent photothermal deicing / frosting capacity. In addition, due to the nano-porous high-absorption structure and wide-spectrum absorption characteristics of the carbon / silicon aerogel, the coating also has excellent ultraviolet resistance and stable silicone oil storage capacity, so that the coating has active and passive ice-repellent durability. The present application provides a new strategy for the recycling and closed use of SLIPS ice-repellent coating and photothermal materials. BRIEF DESCRIPTION OF DRAWINGS
[0031] Figure 1 It is a schematic diagram of the contact angle of the surface of the sample of Example 3.
[0032] Figure 2 It is a schematic diagram of the icing delay time of bare aluminum and the sample of Example 3.
[0033] Figure 3 A schematic diagram of ice adhesion strength of the sample of Example 3 for bare aluminum;
[0034] Figure 4 A schematic diagram of surface temperature change of the sample of Example 3 under irradiation of a near-infrared laser;
[0035] Figure 5 A SEM image of the AM@CAA@SiO2 multi-scale photothermal trap microspheres in the sample of Example 3;
[0036] Figure 6 A schematic diagram of the surface contact angle of the sample of Example 3 after 30 days of ultraviolet irradiation. DETAILED DESCRIPTION
[0037] Example 1
[0038] This example relates to a method for preparing a solid-like smooth anti-icing coating with multi-scale photothermal traps, comprising:
[0039] Step 1, preparation of TAM@CAA@SiO2 multi-scale photothermal trap microspheres:
[0040] 1.1 Disperse the TAM and CAA photothermal nanoparticles into 1 mol / L aqueous polyethyleneimine solution and 0.5 mol / L aqueous NaOH solution, respectively, with a mass ratio of CAA photothermal nanoparticles to aqueous NaOH solution of 1:100 and a mass ratio of TAM to aqueous polyethyleneimine solution of 1:50. After reacting at room temperature for 8 h, each is suction filtered and dried at 80°C for 12 h to obtain cation-modified TAM and anion-modified CAA.
[0041] 1.2 Mix deionized water with the cation-modified TAM and anion-modified CAA in a mass ratio of 100:1:1, and after stirring at room temperature for 4 h, suction filter and dry at 80°C for 12 h to obtain TAM@CAA microspheres.
[0042] 1.3 Add the TAM@CAA microspheres to a mixed solvent of deionized water and anhydrous ethanol in a mass ratio of 1:0.5, with a mass ratio of MTMS to anhydrous ethanol of 1:25, and after the TAM@CAA microspheres are uniformly dispersed, add 10 parts of 0.2 mol / L aqueous ammonia solution, and after stirring at room temperature for 0.5 h, suction filter, then freeze in a -20°C refrigerator for 24 h, and finally perform 72 h of freeze-drying to obtain TAM@CAA@SiO2 multi-scale photothermal trap microspheres.
[0043] Step 2, preparation of a solid-like smooth anti-icing coating with multi-scale photothermal traps, specifically comprising:
[0044] 2.1 Disperse 80 parts of TAM@CAA@SiO2 multi-scale photothermal trap microspheres into 500 parts of ethyl acetate, and after uniform dispersion, continue to add 60 parts of 4,4'-diaminodiphenylmethane curing agent and 100 parts of epoxy E42 resin to form a prepolymer, and then react at room temperature for 8 h, and then react at 60°C for 1.5 h, and then spin coating.
[0045] 2.2 After spin coating and curing at 25°C for 36 h, a solid-like slippery anti-icing coating with multi-scale photothermal traps is obtained.
[0046] The water contact angle of the coating obtained by testing the sample of this example 1 by the hydrophobic angle tester is 103.7±0.5°, and the sliding angle is 3.1±0.3°.
[0047] Example 2
[0048] This example relates to a method for preparing a solid-like slippery anti-icing coating with multi-scale photothermal traps, comprising:
[0049] Step 1, preparation of TAM@CAA@SiO2 multi-scale photothermal trap microspheres:
[0050] 1.1 Disperse TAM and CAA photothermal nanoparticles into 1.5 mol / L polyethyleneimine aqueous solution and 1 mol / L NaOH aqueous solution respectively, the mass ratio of CAA photothermal nanoparticles to NaOH aqueous solution is 1:100, and the mass ratio of TAM to polyethyleneimine aqueous solution is 1:50, and after reacting at room temperature for 10 h, each is filtered and dried at 80°C for 12 h to obtain cation-modified TAM and anion-modified CAA.
[0051] 1.2 Mix deionized water, cation-modified TAM and anion-modified CAA uniformly according to a mass ratio of 100:1:1.5, stir at room temperature for 8 h, filter, and dry at 80°C for 12 h to obtain TAM@CAA microspheres.
[0052] 1.3 Add TAM@CAA microspheres and Na2SiO3 in a mass ratio of 1.5:1 into a mixed solvent of anhydrous ethanol and deionized water in a mass ratio of 1:1, and the mass ratio of Na2SiO3 to anhydrous ethanol is 1:25, then add 10 parts of 0.4 mol / L ammonia solution after the TAM@CAA microspheres are uniformly dispersed, react at room temperature for 1 h, filter, then freeze in a refrigerator at -20°C for 24 h, and finally freeze dry for 72 h to obtain TAM@CAA@SiO2 microspheres.
[0053] Step 2, preparation of a solid-like slippery anti-icing coating with multi-scale photothermal traps, specifically comprising:
[0054] 2.1 Disperse 100 parts of TAM@CAA@SiO2 multi-scale photothermal trap microspheres and 100 parts of SO into 500 parts of ethyl acetate, and after uniform dispersion, continue to add 120 parts of 4,4'-diaminodiphenylmethane curing agent and 100 parts of epoxy E51 resin to form a prepolymer, and then react at room temperature for 8 h, and then react at 80°C for 1 h, and then spin coating.
[0055] 2.2 After spin coating, solidify at 50°C for 24 h to obtain a solid-like slippery anti-icing coating with multi-scale photothermal traps.
[0056] The water contact angle of the coating obtained by testing the sample of this example 2 by a hydrophobic angle tester is 106.2±0.5°, and the sliding angle is 2.9±0.3°.
[0057] Example 3
[0058] This example relates to a method for preparing a solid-like slippery anti-icing coating with multi-scale photothermal traps, comprising:
[0059] Step 1, preparation of TAM@CAA@SiO2 multi-scale photothermal trap microspheres:
[0060] 1.1 Disperse TAM and CAA photothermal nanoparticles into 2 mol / L polyethyleneimine aqueous solution and 1.5 mol / L NaOH aqueous solution respectively, the mass ratio of CAA photothermal nanoparticles to NaOH aqueous solution is 1:100, and the mass ratio of TAM to polyethyleneimine aqueous solution is 1:50, and after reaction at room temperature for 12 h, each is filtered and dried at 80°C for 12 h to obtain cation-modified TAM and anion-modified CAA.
[0061] 1.2 Mix deionized water, cation-modified TAM and anion-modified CAA uniformly according to a mass ratio of 100:1:2, and after stirring at room temperature for 12 h, filter and dry at 80°C for 12 h to obtain TAM@CAA microspheres.
[0062] 1.3 Add TAM@CAA microspheres and TEOS to a mixed solvent of deionized water and anhydrous ethanol in a mass ratio of 1:1.5, and the mass ratio of TEOS to anhydrous ethanol is 1:25, and after the TAM@CAA microspheres are uniformly dispersed, add 10 parts of 0.6 mol / L ammonia solution, and after reaction at room temperature for 1.5 h, filter, then freeze in a-20°C refrigerator for 24 h, and finally freeze dry for 72 h to obtain TAM@CAA@SiO2 microspheres.
[0063] Step 2, preparation of a solid-like slippery anti-icing coating with multi-scale photothermal traps, specifically comprising:
[0064] 2.1 120 parts of TAM@CAA@SiO2 multi-scale photothermal trap microspheres and 100 parts of SO were dispersed into 500 parts of ethyl acetate, and after uniform dispersion, 180 parts of 4, 4'-diaminodiphenyl methane curing agent and 100 parts of epoxy E44 resin were added to form a prepolymer, which was reacted at room temperature for 8 h, and then spin-coated after being reacted at 100°C for 0.5 h.
[0065] 2.2 After spin coating and curing at 80°C for 12 h, a solid-like slippery ice-repellent coating with multi-scale photothermal traps was obtained.
[0066] The water contact angle of the coating obtained by testing the sample of this embodiment 3 with a hydrophobic angle tester is 107.5±0.5°, and the sliding angle is 2.6±0.3°, as shown in Figure 1
[0067] As shown in Figure 2 and Figure 3 The ice adhesion strength of bare aluminum is 208.7 KPa, and the ice delay time is 40 s, while the ice adhesion strength of the sample in embodiment 3 is 9.2 KPa, and the ice delay time is 3180 s, which is 79.4 times longer than that of bare aluminum, and the ice adhesion strength is reduced by 22.7 times, showing excellent ice-repellent performance.
[0068] As shown in Figure 4 , using an 808 nm near-infrared laser as a light source, the light power density was adjusted to 1.0 W / cm 2 , and after irradiation for 20 s, the sample temperature can reach 173°C, showing excellent photothermal performance.
[0069] The SEM image of TAM@CAA@SiO2 multi-scale photothermal trap microspheres is shown in Figure 5 , and the construction of the microsphere surface micro-nano multi-scale structure can endow the coating with high-efficiency photothermal performance.
[0070] As shown in Figure 6 , the surface contact angle of the coating sample after 30 days of ultraviolet irradiation is 103°, which is only reduced by 4.5° compared with that before irradiation, proving that the coating sample has high environmental durability.
[0071] Compared with the prior art, the method combines low-thermal-conductivity hollow thermoplastic acrylate microspheres, nanoporous carbon / silicon aerogel, silicone oil and epoxy resin to synergistically construct a micro-nano multi-scale photothermal trap internal structure and a solid-like smooth surface coating, thereby endowing the coating with an ultra-low water sliding angle, extremely low ice adhesion strength, high photothermal conversion efficiency and environmental tolerance. Compared with bare aluminum, the ice delay time of the application is prolonged by nearly 80 times, and the ice adhesion strength is reduced by 22.7 times. In addition, the photothermal properties of CAA and the multi-scale photothermal trap structure formed by the TAM@CAA@SiO2 microspheres also endow the coating with excellent photothermal deicing / frosting capacity. In addition, due to the nanoporous high-absorption structure and wide-spectrum absorption characteristics of the carbon / silicon aerogel, the coating can also be endowed with excellent ultraviolet resistance and stable silicone oil storage capacity, ultimately making the coating have active and passive anti-icing durability. It provides a new strategy for the closed-loop utilization of SLIPS ice-repellent coatings and photothermal materials.
[0072] The specific embodiments described above can be modified in various ways by those skilled in the art without departing from the principles and spirit of the application. The scope of protection of the application is subject to the claims and is not limited by the specific embodiments described above. Each implementation within the scope of the application is subject to the constraints of the application.
Claims
1. A method for preparing a solid-like slippery anti-icing coating with multi-scale photothermal traps, characterized in that, Anionic modified carbon aerogel (CAA) photothermal nanoparticles were deposited on the surface of cationic modified hollow thermoplastic acrylate microspheres (TAM). After filtration and drying, TAM@CAA microspheres were obtained. Silica (SiO2) aerogel was then grown in situ on the surface of the microspheres using an alkaline-catalyzed sol-gel method. After filtration and freeze-drying, TAM@CAA@SiO2 multi-scale photothermal trap microspheres were obtained. The multi-scale photothermal trap microspheres were then dispersed with silicone oil (SO) and a curing agent in an organic solvent containing epoxy resin to fully react and form a prepolymer. Finally, the prepolymer was spin-coated and cured to obtain a solid-like slippery anti-icing coating with multi-scale photothermal traps.
2. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 1, characterized in that, The anionic modification refers to dispersing carbon aerogel (CAA) photothermal nanoparticles in an anionic modification solution, reacting at room temperature for 8-12 hours, and then drying at 80°C for 12 hours.
3. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 2, characterized in that, The anion-modifying solution is an aqueous solution of NaOH with a concentration of 0.5-1.5 mol / L; The mass ratio of the CAA photothermal nanoparticles to the NaOH aqueous solution is 1:
100.
4. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 1, characterized in that, The aforementioned cationic modification refers to dispersing TAM in a cationic modification solution, reacting at room temperature for 8-12 hours, and then drying at 80°C for 12 hours.
5. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 4, characterized in that, The cationic modified solution is an aqueous solution of polydiallyldimethylammonium chloride (PDDA), polyethyleneimine (PEI), or cationic polyacrylamide (CPAM) with a concentration of 1-2 mol / L; The mass ratio of TAM to the cationic modified aqueous solution is 1:
50.
6. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 1, characterized in that, The deposition process involves dispersing cationic modified TAM and anionic modified CAA in a solvent at a mass ratio of 1:1-2 (cationic modified TAM: anionic modified CAA), using deionized water as the reaction solvent, for a reaction time of 4-12 hours. After the reaction is complete, the mixture is dried at 80°C for 12 hours to obtain TAM@CAA microspheres.
7. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 1, characterized in that, The alkaline catalytic sol-gel method refers to the following: after mixing and dispersing TAM@CAA microspheres with a silicon source in a mixed solution of deionized water and ethanol, an alkaline catalyst is further added and the mixture is allowed to react fully.
8. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 1, characterized in that, The complete reaction refers to the following: after growing SiO2 aerogel in situ on the TAM@CAA surface for 0.5-1.5 hours, filtering it, freezing it in a -20°C freezer for 24 hours, and then freeze-drying it for 72 hours.
9. The method for preparing a solid-like slippery anti-icing coating with a multi-scale photothermal trap according to claim 1, characterized in that, The aforementioned complete reaction to form the prepolymer refers to reacting at room temperature for 8 hours, followed by reacting at 60-100℃ for 0.5-1.5 hours.
10. A solid-like slippery anti-icing coating with multi-scale photothermal traps, characterized in that, Prepared by the method according to any one of claims 1-9.